Synthesis of Some New Dimers as Constructive of Nano Machines - Ghaffar Ebadi, Abdol; Alami, Somaye (Asian Journal of Chemistry, 2012)
In this research work, a part of nano machines is synthesized, based on interlocked macrocycle named rotaxanes, pseudorotaxanes, knots and catenanes which constitute any passive or active structure capable of actuation, mesoscale molecular electronic devices, sensing, signaling, information processing, intelligence, swarm behaviour at the nano scale. The dibenzosulfide (1) was obtained by p-cresol and sulfur dicholorie in dry petroleum ether in 50 % yield. Treatment of compound (1) with methyl choloroacetate in presence of K2CO3 and KI at refluxed dry acetone gave diester (2) in 98 % yield. For synthesis of macrocycle (3), diester (2) and diethylene triamine was refluxed in dry methanol and gave dibenzosulfide 16-crown-6 in 75 % yields. Bis azacrown (4) was synthesized by macrocycle (3) and decanocoyl dicholoride in dry CH2Cl2 and was refluxed in presence of Et3N in good yield and then purified by column chromatography.